EFFECT OF WOOD STACKING ON PRODUCTIVITY AND COST OF FOREST EXTRACTION AND LOADING - Masioli, William; da Silva Lopes, Eduardo; Pagnussat, Millana Bürger; Garsztka, Luiz Carlos (Floresta, 2023)
Due to the need to implement new operational procedures that provide productivity gains and cost reduction in wood harvesting and logistics, the objective of this study was to evaluate the effect of wood stacking on productivity and costs of forest extraction and loading operations. The study was carried out in eucalyptus plantations, where the extraction of wood with the forwarder and the loading of vehicles with the forest loader were evaluated. Three log stacking models on the edge of the stand were evaluated: control, inverted and adjacent, with variations in the alignment and distance of the logs concerning the edge of the stand. A study of the times and movements of the operations was carried out, determining the productivity (m³.h-1) and the production cost (R$.m-3) of the forestry operations. The data were compared using the Tukey test (α=5%) for parametric data and the Kruskal-Wallis test (α=5%) for non-parametric data, and the effect of different extraction distances was also verified using equations. The inverted stacking model contributed to the increase in extraction productivity, while the adjacent model in loading, with a reduction in production cost of around 22.1%. Simultaneously analyzing both wood stacking models, the standard model adopted by the forestry company was better with a 6.1% reduction in costs compared to the others. The productivity equations showed that the inverted stacking model contributed to the forwarder's higher performance at distances up to 140 m. The study showed that wood stacking models affect forestry operations and should be considered in operational planning.